Fontes e niveis de fibra na dieta de frangas de postura comercial - Royer, Ana Flávia Basso (2018)
Dietary fibers constitute a significant part of all vegetable diets and vary in amount and structure in different ingredients. Has featured in the formulation of feed for poultry, seen the benefits in the development of the digestive and reproductive systems and on the behaviour of birds. However, knowledge of the relationship of the fiber and nutrient utilization needs to be better understood in poultry nutrition, especially in the quality of eggs, and optimal levels of inclusion in commercial diets. Thus, the objective of evaluating the inclusion of crude fiber in the diet of laying hens in light creates, recreates, about weight and body development characteristics, development of digestive organs, and reproductive behavior. The experiment was conducted at the Federal University of Goias, Goiania – GO, using vipul Bovans White line 300, in completely randomized design with factorial arrangement 2 x 2 +1, being two levels of crude fiber in the diet (3.0% and 3.5% from FB) two sources of fiber (wheat bran and bagasse) and a treatment witness (feed corn and soybean meal), totaling five treatments, with six repetitions of 10 birds in each stage of builds. We evaluated patterns of behavior and well-being. The use of crude fiber in the feeding of birds did not change the behavior of the birds, but improved the conditions of well-being. The experiment was carried out at the Federal University of Goiás, Goiânia – GO, using vipul Bovans White line 300, in completely randomized design with factorial arrangement 2 x 2 +1, being two levels of crude fiber in the diet (3.0% and 3.5% from FB) two sources of fiber (wheat bran and bagasse) and a treatment witness (feed corn and soybean meal), totaling five treatments, with six repetitions of 10 birds in each stage of builds. We assessed the performance, carcass and organs relative weight, digestibility of DM, CP, NDF and FDA. The inclusion of 3.0% crude fiber and wheat bran improves the development of intestines of birds. The use of bagasse improves the digestibility of dietary neutral detergent fiber. The experiment II was held at Universidade Federal da Grande Dourados, gilded-MS, using 360 White Bovans line vipul created from the first week of age until the 18th week, in completely randomized design with factorial arrangement 2x2+1, being two levels of crude fiber in the diet (3.0% and 3.5% FB) two sources of fiber (wheat bran and bagasse) and a treatment witness (feed corn and soybean meal), totaling five treatments, with six repetitions of each birds in 12 creates and 10 birds in rearing phase. We assessed the performance, carcass and organs relative weight, digestibility of DM, CP, NDF and FDA. The use of bagasse damages metabolizabilidade of diets, especially with the use of 3.0% FB. However, on the birds that use rebuilds food increases the size of the large intestine, gizzard and oviduct. And the use of wheat bran, with the inclusion of 3.0 and 3.5% FB, reduces the age at first egg.